Small-fragment genomic libraries for the display of putative epitopes from clinically significant pathogens - T. Henics; B. Winkler; U. Pfeifer; S.R. Gill; M. Buschle; A. von Gabain; A.L. Meinke (BioTechniques)
Taking advantage of whole genome sequences of bacterial pathogens in many thriving diseases with global impact, we developed a comprehensive screening procedure for the identification of putative vaccine candidate antigens. Importantly, this procedure relies on highly representative small-fragment genomic libraries that are expressed to display frame-selected epitope-size peptides on a bacterial cell surface and to interact directly with carefully selected disease-relevant high-titer sera. Here we describe the generation of small-fragment genomic libraries of Gram-positive and Gram-negative clinically significant pathogens, including Staphylococcus aureus and Staphylococcus epidermidis, Streptococcus pyogenes, Streptococcus agalactiae, and Streptoococcus pneumoniae, Enterococcus faecalis, Helicobacter pylori, Chlamydia pneumoniae, the enterotoxigenic Escherichia coli, and Campylobacter jejuni. Large-scale sequencing revealed that the libraries, which provide an average of 20-fold coverage, were random and, as demonstrated with two S. aureus libraries, highly representative. Consistent with the comprehensive nature of this approach is the identification of epitopes that reside in both annotated and putatively novel open reading frames. The use of these libraries therefore allows for the rapid and direct identification of immunogenic epitopes with no apparent bias or difficulty that often associate with conventional expression methods.